(untitled) (Texas Journal of Medical Science, 2025)
This article discusses the issues of using gene therapy in the treatment of oncological diseases in Uzbekistan, new approaches implemented in this area, and local problems conditions. The global successes of gene therapy and such factors as infrastructure, personnel qualifications, financial opportunities in Uzbekistan will be analyzed. The article presents information on the research conducted in this area, their results, discussions and directions for future development. The main obstacles to the implementation of gene therapy at the local level are identified and solutions are proposed. The article serves as a useful resource for health professionals, researchers and policy makers.